Modified separator and preparation method and application thereof

CN120709659BActive Publication Date: 2026-11-03JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511041321.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-28
Publication Date
2026-11-03
Estimated Expiration
2045-07-28

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators are prone to shrinkage at high temperatures, leading to safety issues, and cannot effectively suppress lithium dendrite growth, affecting the battery's cycle life and safety.

Method used

Multiple first coating regions containing MS2 and multiple second coating regions containing ceramic particles are alternately and staggered on the surface of a traditional polymer separator to form a modified coating with a specific structure, which improves the lithium affinity and thermal stability of the separator and forms a stable interface layer on the negative electrode surface, thereby improving the interface contact of the battery.

Benefits of technology

It improves the liquid absorption capacity of the separator, reduces the internal resistance of the battery, inhibits lithium dendrite growth, and enhances the cycle performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120709659B_ABST
    Figure CN120709659B_ABST
Patent Text Reader

Abstract

The present application relates to a modified diaphragm and its preparation method and application, the modified diaphragm includes base film and the modified coating arranged on the base film at least one side along the thickness direction, the modified coating includes multiple first coating areas and multiple second coating areas, the first coating area and the second coating area are staggered on the length and width direction of the base film;The first coating area contains MS2, and the second sub-coating area contains ceramic particles.The present application can effectively improve the porosity of the diaphragm, improve its liquid absorption capacity by alternately staggered setting the first coating area containing MS2 and the second coating area containing ceramic particles on the diaphragm surface, and the prepared modified diaphragm has higher conductivity and tensile strength, which can effectively improve the cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to a modified separator, its preparation method, and its application. Background Technology

[0002] With the widespread application of lithium-ion batteries in electric vehicles, energy storage systems, and portable electronic devices, the requirements for their energy density, cycle life, and safety performance are increasing. As a key component of lithium-ion batteries, the separator is a physical barrier that isolates the positive and negative electrodes to prevent short circuits. It not only needs to possess good ion conductivity and electronic insulation but also needs to maintain structural stability under extreme conditions such as high temperature and high pressure to prevent battery short circuits or thermal runaway. Furthermore, its structure and chemical properties have a significant impact on lithium dendrite growth and the stability of the negative electrode interface.

[0003] Currently, commercially available polyethylene (PE) and polypropylene (PP) separators exhibit poor electrolyte wettability and uneven pore distribution, easily leading to localized concentration of lithium-ion flow and uneven lithium deposition, resulting in the continuous growth of lithium dendrites. Furthermore, these membrane materials also have poor thermal stability, easily shrinking at high temperatures, potentially causing safety issues. Current improvements primarily involve coating the separator surface with inorganic nano-ceramic particles, such as nano-silica and alumina, to improve thermal stability and electrolyte wettability. However, these coatings lack sufficient lithium affinity and cannot effectively suppress dendrite growth in lithium-ion batteries, nor can they solve the safety problems (especially lithium metal batteries) caused by the continuous growth of lithium dendrites.

[0004] Therefore, there is an urgent need for a separator that can effectively suppress lithium dendrite growth and improve the instability of the negative electrode interface, thereby improving the cycle life of lithium-ion batteries. Summary of the Invention

[0005] To address the aforementioned issues, this invention provides a modified separator, its preparation method, and its application. By alternately and staggeredly setting multiple first coating regions containing MS2 and multiple second coating regions containing ceramic particles on the surface of the base membrane, the lithium affinity and thermal stability of the separator are effectively improved, and the liquid absorption capacity of the separator is further enhanced, which is beneficial for reducing the internal resistance of the battery. At the same time, the MS2 on the surface of the modified separator can participate in the construction of the negative electrode SEI film, forming a stable interface protective layer on the negative electrode surface, achieving uniform lithium deposition, inhibiting the growth of lithium dendrites, and improving the cycle performance of the battery.

[0006] This invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a modified diaphragm, the modified diaphragm comprising a base film and a modified coating disposed on at least one side of the base film along its thickness direction;

[0008] The modified coating includes multiple first coating regions and multiple second coating regions, wherein the first coating regions and the second coating regions are staggered in the length and width directions of the base film;

[0009] The first coating region contains MS2, where M is selected from one or more metals in group IVB; the second coating region contains ceramic particles.

[0010] Furthermore, the base film is made of one or more of polyethylene, polypropylene, and polyetherimide; more preferably, the thickness of the base film is 5-20 μm.

[0011] Furthermore, the total area of ​​the plurality of first coating regions accounts for 40%-60% of the total area of ​​the modified coating; more preferably, the total area of ​​the plurality of first coating regions is the same as that of the plurality of second coating regions.

[0012] Furthermore, the thickness of the first coating region is preferably 1-20 μm; the thickness of the second coating region is preferably 1-10 μm.

[0013] Furthermore, the MS2 is preferably TiS2.

[0014] Furthermore, the ceramic particles include one or more of the following: alumina, silicon oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, iron oxide, and titanium oxide.

[0015] Furthermore, both the first coating area and the second coating area are rectangles with the same area and a side length of 5-10 mm; more preferably, the first coating area and the second coating area are squares with the same area.

[0016] Further, the modified diaphragm includes a base film and a modified coating disposed on both sides of the base film along the thickness direction; or, the modified diaphragm includes a base film and a modified coating disposed on one side of the base film along the thickness direction, and a ceramic coating disposed on the other side of the base film along the thickness direction.

[0017] Furthermore, the ceramic coating is made of the same material as the second coating region.

[0018] A second aspect of the present invention provides a method for preparing a modified diaphragm, comprising the following steps:

[0019] S1. Prepare a first coating slurry and a second coating slurry; the first coating slurry contains MS2, where M is selected from one or more metal elements in group IVB; the second coating slurry contains ceramic particles;

[0020] S2. The first coating slurry and the second coating slurry are respectively coated on the surface of the base film according to a preset pattern to form a modified coating, and the modified diaphragm is obtained after drying; the preset pattern includes a plurality of first coating areas and a plurality of second coating areas; the first coating area is used to coat the first coating slurry, and the first coating area is formed after drying; the second coating area is used to coat the second coating slurry, and the second coating area is formed after drying.

[0021] Further, in step S1, the first coating slurry is obtained by mixing MS2, calcium hydroxide, polyacrylate, carboxymethyl cellulose, and water in a mass ratio of (20-40):(5-6):(4-5):(8-10):(15-30); the second coating slurry is obtained by mixing ceramic particles, calcium hydroxide, polyacrylate, carboxymethyl cellulose, and water in a mass ratio of (10-20):(5-6):(4-5):(8-10):(15-30).

[0022] Further, in step S1, MS2 is TiS2;

[0023] The preparation method of TiS2 includes the following steps: mixing titanium powder and sulfur powder at a molar ratio of 1:(5-10) to obtain a mixed powder, and then transferring it to an inert atmosphere for heating reaction to obtain TiS2; the heating reaction temperature is 100-150℃, and the heating reaction time is 12-52h.

[0024] Furthermore, in step S2, the coating method includes transfer printing and / or spraying, scraping, spin coating or roller coating using a mask.

[0025] A third aspect of the present invention provides a secondary battery comprising the modified separator described in the first aspect or the modified separator prepared by the preparation method described in the second aspect.

[0026] Furthermore, the secondary battery includes a negative electrode.

[0027] Furthermore, when the modified separator comprises a base film and a modified coating disposed on one side of the base film along the thickness direction, and a ceramic coating disposed on the other side of the base film along the thickness direction, in the secondary battery, the side of the modified separator where the modified coating is located is in contact with the negative electrode sheet.

[0028] More preferably, the negative electrode is a lithium metal negative electrode.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0030] 1. This invention provides a modified separator. By alternately and staggeredly setting multiple first coating regions containing MS2 and multiple second coating regions containing ceramic particles on the surface of a traditional polymer separator, the lithium affinity and thermal stability of the separator can be effectively improved, which is beneficial for suppressing lithium dendrite growth and improving battery safety. Moreover, under the synergistic effect of coating materials and structural design, the modified separator's electrolyte absorption capacity is effectively improved compared to the traditional polymer separator. Specifically, the MS2 contained in the first coating region can improve the wettability of the separator to the electrolyte, and the ceramic particles contained in the second coating region can improve the electrolyte absorption capacity of the separator. Furthermore, the staggered structure of the first and second coating regions is beneficial for improving the porosity of the separator. Under the synergistic effect of the above materials and structure, the electrolyte absorption rate of the separator can be effectively increased, thereby improving ionic conductivity and interfacial contact, and thus effectively reducing the internal resistance of the battery. In addition, compared with traditional polymer membranes or ceramic composite membranes, the modified membrane prepared by this invention can effectively improve the interface problem between the negative electrode and the electrolyte. MS2 in the modified coating can participate in the construction of the negative electrode SEI film, forming a stable interface protective layer on the negative electrode surface, enhancing the stability of interface ion conduction, achieving uniform lithium deposition, inhibiting the growth of lithium dendrites, and improving the cycle performance of the battery.

[0031] 2. The modified separator described above has high liquid absorption rate, low resistance and high tensile strength, and lithium-ion batteries constructed with it exhibit better cycle performance. Attached Figure Description

[0032] Figure 1 This is a schematic diagram of the cross-section of a modified diaphragm provided by the present invention;

[0033] Figure 2 A schematic diagram of the structure of the modified coating surface of a modified diaphragm provided by the present invention;

[0034] In the figure, 1 is the base film, 2 is the modified coating, 21 is the first coating area, and 22 is the second coating area. Detailed Implementation

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items. "Comprising" or "containing" as used herein means that it may include or contain other components in addition to the stated components. "Comprising" or "containing" as used herein may also be replaced with the closed form "is" or "consisting of".

[0036] As described in the background section, lithium dendrite formation and interface issues in lithium-ion batteries limit further improvements in their lifespan. The separator, as a key component of lithium-ion batteries, significantly impacts lithium dendrite growth and negative electrode interface stability. However, traditional polymer separators suffer from poor thermal stability and insufficient mechanical strength. Furthermore, their uneven pore size distribution and poor electrolyte wettability easily lead to uneven lithium deposition, resulting in continuous lithium dendrite growth and severely affecting battery safety and cycle life. While coating polymer separators with inorganic nano-ceramic particles can improve thermal stability and electrolyte wettability, these coatings lack sufficient lithium affinity, failing to effectively inhibit lithium dendrite growth, improve interface issues, or resolve the safety problems caused by continuous lithium dendrite growth.

[0037] To address the aforementioned problems, this invention provides a modified diaphragm, comprising a base film and a modified coating disposed on at least one side of the base film along its thickness direction.

[0038] The modified coating includes multiple first coating regions and multiple second coating regions, wherein the first coating regions and the second coating regions are staggered in the length and width directions of the base film;

[0039] The first coating region contains MS2, where M is selected from one or more metals in group IVB; the second coating region contains ceramic particles.

[0040] To address the lithium dendrite and interface problems present in current lithium-ion batteries, this invention provides a modified separator. This modified separator is achieved by alternately and staggeredly depositing multiple first coating regions containing MS2 and multiple second coating regions containing ceramic particles on the surface of a conventional polymer separator (base film), forming a modified coating with a specific material composition and structure.

[0041] In terms of materials: (1) The MS2 contained in the first coating region has high ionic conductivity and electrochemical stability, and can form good interfacial contact with the electrode, which is beneficial to reducing interfacial impedance and improving the rate performance of the battery. In addition, MS2 has good thermal stability with the positive electrode material, which is beneficial to improving the safety of the battery. Furthermore, when the separator surface and the negative electrode surface come into contact after the battery is assembled, MS2 can participate in the construction of the negative electrode SEI film, which can not only enhance the ion conduction stability and inhibit dendrite growth, further improving the safety performance of the battery, but also alleviate the side reactions between the electrode material surface and the electrolyte, and improve the cycle performance of the battery. (2) The ceramic particles contained in the second coating region can improve the liquid absorption capacity of the separator, which is beneficial to improving ionic conductivity and interfacial contact, and reducing the internal resistance of the battery; at the same time, the presence of ceramic particles can improve the anti-shrinkage performance of the modified separator, which is beneficial to improving the safety performance of the battery.

[0042] Structurally, unlike a single coating prepared by uniformly mixing different functional materials, the modified coating on the base film in this invention consists of multiple first coating regions containing MS2 and multiple second coating regions containing ceramic particles, staggered along the length and width of the base film. This effectively avoids the problem of functional interference between different functional materials caused by uniform mixing. Furthermore, the mesh-like support structure formed by the different coating regions on the base film surface allows for simultaneous improvement in the tensile strength, puncture resistance, and shrinkage resistance of the separator in both the transverse and longitudinal directions. This avoids mechanical weaknesses caused by unidirectional alternation and optimizes the lithium-ion transport path, reducing concentration polarization and effectively suppressing dendrite growth and penetration. In addition, the staggered arrangement increases the porosity of the separator, further enhancing its electrolyte absorption rate.

[0043] With the synergistic effect of the above materials and structures, the modified separator provided by the present invention has high liquid absorption rate, low solution resistance and high tensile strength, which can effectively suppress lithium dendrite growth and improve the stability of the electrode interface, thereby significantly improving the safety and cycle performance of lithium-ion batteries containing the above modified separator.

[0044] In this invention, the material of the base membrane can be selected from one or more of polyethylene, polypropylene, and polyetherimide, or other polymer materials commonly used in the field for diaphragms; preferably, the thickness of the base membrane is 5-20 μm, such as 5 μm, 7 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, etc., including but not limited to the thickness values ​​listed above.

[0045] In this invention, the total area ratio of multiple first coating regions in the modified coating affects the content and distribution area of ​​MS2 material and ceramic particles in the modified coating. If the total area ratio of the first coating regions is too low, the content and distribution of MS2 material in the modified coating will be insufficient, failing to effectively participate in the construction of the negative electrode SEI film and affecting the formation of the interface protective layer. Simultaneously, the total area ratio of the first coating regions should not be too high, otherwise it will not only affect the overall anti-shrinkage performance of the separator but also lead to an excessively long lithium-ion transport path, affecting the lithium-ion insertion and extraction rates. Preferably, the percentage of the total area of ​​the multiple first coating regions to the total area of ​​the modified coating is controlled between 40% and 60%, such as 40%, 45%, 50%, 55%, 60%, etc., including but not limited to the area ratios listed above; more preferably, it is 50%, that is, the total area of ​​the multiple first coating regions is the same as the total area of ​​the multiple second coating regions.

[0046] In this invention, the thickness of the first coating region is preferably 1-20 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc., including but not limited to the thickness values ​​listed above; the thickness of the second coating region is preferably 1-10 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc., including but not limited to the thickness values ​​listed above.

[0047] In this invention, M is preferably Ti, that is, MS2 is TiS2. Titanium sulfide has electrical conductivity and can form a Ti-Li-S alloy interface protective layer with the negative electrode SEI film, which is beneficial to suppress dendrite growth and reduce the occurrence of interface side reactions. In addition, titanium sulfide is also beneficial to improve the wettability of the membrane to the electrolyte and its thermal stability.

[0048] In this invention, the ceramic particles can be selected from one or more of alumina, silicon oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, iron oxide, and titanium oxide, including but not limited to the types listed above. They can be conventionally replaced according to functional requirements, and the conventional ceramic materials replaced are also within the scope of protection of this application.

[0049] In this invention, both the first coating area and the second coating area are rectangles with the same area. Preferably, the side length is 5-10mm, such as 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, etc., which is conducive to the uniform distribution of the first coating area and the second coating area on the modified coating surface, and improves the functionality and synergistic effect of different areas. More preferably, the first coating area and the second coating area are squares with the same area.

[0050] In this invention, the modified separator comprises a base film and modified coatings disposed on both sides of the base film along its thickness direction. More preferably, when the modified separator comprises a base film and modified coatings disposed on both sides of the base film along its thickness direction, the projection of the first coating region in the modified coating on the upper surface of the base film in the vertical direction coincides with the projection of the second coating region in the modified coating on the lower surface of the base film in the vertical direction, further balancing the mechanical properties of each region of the modified separator. Alternatively, the modified separator comprises a base film and a modified coating disposed on one side of the base film along its thickness direction, and a ceramic coating disposed on the other side of the base film along its thickness direction; in some preferred embodiments, the ceramic coating is made of the same material as the second coating region in the modified coating.

[0051] The present invention also provides a method for preparing the above-mentioned modified diaphragm, comprising the following steps:

[0052] S1. Prepare a first coating slurry and a second coating slurry; the first coating slurry contains MS2, where M is selected from one or more metal elements in group IVB; the second coating slurry contains ceramic particles;

[0053] S2. The first coating slurry and the second coating slurry are respectively coated on the surface of the base film according to a preset pattern to form a modified coating, and the modified diaphragm is obtained after drying; the preset pattern includes a plurality of first coating areas and a plurality of second coating areas; the first coating area is used to coat the first coating slurry, and the first coating area is formed after drying; the second coating area is used to coat the second coating slurry, and the second coating area is formed after drying.

[0054] In some preferred embodiments, in step S1, the first coating slurry is obtained by mixing MS2, calcium hydroxide, polyacrylate, carboxymethyl cellulose, and water in a mass ratio of (20-40):(5-6):(4-5):(8-10):(15-30); the second coating slurry is obtained by mixing ceramic particles, calcium hydroxide, polyacrylate, carboxymethyl cellulose, and water in a mass ratio of (10-20):(5-6):(4-5):(8-10):(15-30).

[0055] In some preferred embodiments, in step S1, MS2 is TiS2, and the preparation method of TiS2 includes the following steps: mixing titanium powder and sulfur powder at a molar ratio of 1:(5-10) to obtain a mixed powder, and then transferring it to an inert atmosphere for heating reaction to obtain TiS2; wherein, the heating reaction temperature is preferably 100-150℃, and the heating reaction time is preferably 12-52h.

[0056] In some preferred embodiments, in step S2, the coating method includes transfer printing and / or spraying, scraping, spin coating or roller coating using a mask.

[0057] In addition, the present invention also provides a secondary battery comprising the above-described modified separator.

[0058] In some preferred embodiments, the secondary battery further includes a negative electrode sheet. When the modified separator includes a base film and a modified coating disposed on one side of the base film along the thickness direction, and a ceramic coating disposed on the other side of the base film along the thickness direction, in the secondary battery, the side of the modified separator containing the modified coating is in contact with the negative electrode sheet.

[0059] The present invention will be further described below with reference to specific embodiments and accompanying drawings, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0060] Example 1

[0061] This embodiment relates to the preparation of a modified diaphragm, and the specific operation is as follows:

[0062] (1) Preparation of TiS2: Using 99.99% titanium powder and sulfur powder as raw materials, the molar ratio of iron powder to sulfur powder is 1:8. The weighed titanium powder and sulfur powder are wrapped separately in weighing paper and placed in plastic bags. The packaged titanium powder, sulfur powder, quartz tube and sealant are placed in a glove box. In the glove box, titanium powder and sulfur powder are sequentially placed into the quartz tube. After standing for 12 hours, the quartz stopper is closed and the quartz tube is sealed with sealant. Then the sealed quartz tube is placed under a 120℃ heat lamp for 4-6 hours. After the sealant has completely solidified, it is placed in a tube furnace. After vacuuming three times, argon gas is introduced and the reaction is sealed in the tube furnace at 120℃ for 48 hours. After cooling to room temperature, a black powder sample is obtained in the quartz tube, which is titanium disulfide.

[0063] (2) Preparation of the first coating slurry: Water, calcium hydroxide, polyacrylate, TiS2 powder and CMC are mixed evenly in a mass ratio of 25:5:4:30:8 to obtain the first coating slurry.

[0064] Preparation of the second coating slurry: Water, calcium hydroxide, polyacrylate, alumina and CMC are mixed evenly in a mass ratio of 20:5:4:15:8 to obtain the second coating slurry.

[0065] (3) Using a mask, the first coating slurry is applied to one side of a PE base film (7μm polyethylene film). After drying, a second coating slurry is applied to the same surface of the base film using a mask. After drying, a modified coating is formed. Then, the same coating operation is performed on the other side of the base film. After drying, a modified coating is formed, resulting in a modified diaphragm (e.g., Figure 1 (As shown).

[0066] The modified diaphragm prepared in this embodiment includes a base membrane and modified coatings disposed on both sides of the base membrane. The modified coatings include an equal number of first coating regions and second coating regions, such as... Figure 2 As shown, the first coating area and the second coating area are staggered in the length and width directions of the base film; both the first coating area and the second coating area are squares with a side length of 8mm, the thickness of the first coating area is 5μm, and the thickness of the second coating area is 5μm.

[0067] Example 2

[0068] This embodiment relates to the preparation of a modified diaphragm, which differs from Embodiment 1 only in that: the first coating area is a rectangle of 5mm×4mm and the second coating area is a rectangle of 5mm×6mm, that is, the total area of ​​the first coating area accounts for 40% of the area of ​​the modified coating; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0069] Example 3

[0070] This embodiment relates to the preparation of a modified diaphragm, which differs from Embodiment 1 only in that: the first coating area is a rectangle of 5mm×6mm and the second coating area is a rectangle of 5mm×4mm, that is, the total area of ​​the first coating area accounts for 60% of the area of ​​the modified coating; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0071] Example 4

[0072] This embodiment relates to the preparation of a modified diaphragm, which differs from Embodiment 1 only in that: the first coating area is a rectangle of 5mm×3mm and the second coating area is a rectangle of 5mm×7mm, that is, the total area of ​​the first coating area accounts for 30% of the area of ​​the modified coating; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0073] Example 5

[0074] This embodiment relates to the preparation of a modified diaphragm, which differs from Embodiment 1 only in that: the first coating area is a rectangle of 5mm×7mm and the second coating area is a rectangle of 5mm×3mm, that is, the total area of ​​the first coating area accounts for 70% of the area of ​​the modified coating; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0075] Example 6

[0076] This embodiment relates to the preparation of a modified diaphragm, which differs from Embodiment 1 only in that: both the first coating region and the second coating region are squares with a side length of 10 mm; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0077] Example 7

[0078] This embodiment relates to the preparation of a modified diaphragm, which differs from Embodiment 1 only in that: the first coating area and the second coating area are both squares with a side length of 15mm; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0079] Example 8

[0080] This embodiment relates to the preparation of a modified diaphragm, differing from Example 1 only in that an equal amount of zirconium sulfide is used to replace TiS2, wherein the zirconium sulfide is prepared as follows:

[0081] Zirconium metal powder and elemental sulfur were mixed at a molar ratio of 1:1.1 and ball-milled for 12 hours. The mixture was then calcined under an inert atmosphere: first, the temperature was increased to 300°C at a rate of 5°C / min and held for 1 hour to promote the full vaporization and penetration of sulfur; then, the temperature was increased to 800-950°C at a rate of 3°C / min and held for 6-8 hours to ensure the full diffusion of zirconium and sulfur atoms. The remaining powder after calcination was zirconium sulfide.

[0082] The remaining operations were the same, and the corresponding modified diaphragm was prepared.

[0083] Comparative Example 1

[0084] This comparative example relates to the preparation of a modified diaphragm, which differs from Example 1 only in that the modified coating consists of a first TiS2 coating disposed on both sides of the base membrane and a second ceramic coating disposed on the side of the first TiS2 coating away from the base membrane, wherein the thickness of the first TiS2 coating is 2.5 μm and the thickness of the second ceramic coating is 2.5 μm; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0085] Comparative Example 2

[0086] This comparative example relates to the preparation of a modified diaphragm, which differs from Example 1 only in that the modified coating consists of a first ceramic coating disposed on both sides of the base membrane and a second TiS2 coating disposed on the side of the first ceramic coating away from the base membrane, wherein the thickness of the first ceramic coating is 2.5 μm and the thickness of the second TiS2 coating is 2.5 μm; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0087] Comparative Example 3

[0088] This comparative example relates to the preparation of a modified diaphragm. The only difference from Example 1 is that the first coating slurry and the second coating slurry are mixed evenly to obtain a mixed slurry. The mixed slurry is coated on one side of the base film and dried to form a modified coating with a thickness of 5 μm. All other aspects are the same, and the corresponding modified diaphragm is prepared.

[0089] Comparative Example 4

[0090] This comparative example relates to the preparation of a modified diaphragm, which differs from Example 1 only in that: the first coating region and the second coating region are staggered only in the length direction of the base film; both the first coating region and the second coating region are the same rectangle, with the length consistent with the width of the base film and the width of both being 8 mm; the thickness of the first coating region is 5 μm and the thickness of the second coating region is 5 μm; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0091] Comparative Example 5

[0092] This comparative example relates to the preparation of a modified diaphragm. The only difference from Example 1 is that an equal amount of ZnS is used to replace TiS2 in the preparation of the first coating slurry; all other aspects are the same, and the corresponding modified diaphragm is prepared.

[0093] Application and performance testing

[0094] (1) The modified membranes prepared in the above embodiments and comparative examples were subjected to the following performance tests, as detailed below:

[0095] Porosity test: After immersing the weighed modified membrane (Wd) in n-butanol for 2 hours, remove it and gently blot the liquid off its surface with filter paper. Then weigh it again (Ww). The mass of n-butanol absorbed by the modified membrane, Wb = Ww - Wd, can be obtained. The pore volume of the modified membrane can be obtained by dividing the mass of n-butanol (Wb) by the density of n-butanol (ρb). The ratio of this volume to the dry membrane volume (Vp) is the porosity P of the modified membrane. The calculation formula is: P% = (Ww - Wd) / (Vp × ρb).

[0096] Liquid absorption rate test: The sample size was 2×2cm, the electrolyte was 1mol / L LiPF6, and the solvent of the electrolyte was a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a mass ratio of 1:1:1. The liquid absorption of the membrane was determined using the electrolyte. A small piece of modified membrane was taken, dried, and weighed (M1). The modified membrane was then immersed in the electrolyte for 30 minutes until it had fully absorbed the electrolyte, after which it was removed. The electrolyte on the surface of the modified membrane was gently absorbed with filter paper, and the weight (M2) was measured. The liquid absorption rate (w) was calculated using the formula: w% = (M2 - M1) / M1 × 100%.

[0097] Tensile strength test: testing equipment: tensile tester; method: sample size TD×MD=15mm×100mm, tested according to GB / T1040.3-2006 standard.

[0098] Conductivity test: The solution resistance R is measured using the AC impedance method. L In fact, R L This includes all ohmic resistances in the system, such as the high-resistivity film on the electrode surface, the ohmic resistance of the diaphragm, and the ohmic resistance of the electrode itself. However, since the diaphragm resistance is the main component of the solution resistance, it is approximated as R. m =R L The diaphragm thickness d was measured using a micrometer screw gauge, and S was the electrode area, which was always 1 cm². 2 (The electrode is a 1×1cm stainless steel sheet), the conductivity calculation formula is: к=d / (R L ·S).

[0099] The test results are shown in Table 1 below:

[0100] Table 1

[0101]

[0102]

[0103] As shown in Table 1, the modified membranes prepared in Examples 1-8 by alternately and staggeredly setting multiple first coating regions containing MS2 and multiple second coating regions containing ceramic particles on the membrane surface exhibit high porosity, high liquid absorption rate, high conductivity, and high tensile strength. Specifically, if the total area of ​​the first or second coating regions in the modified coating is too large or too small (Examples 1-5), or if the area of ​​a single first or second coating region is too large or too small (Examples 1, 6, 7), it will affect the liquid absorption rate, conductivity, and tensile strength. Preferably, when the size of the first and second coating regions in the modified coating is appropriate and their total area is the same, the performance is better (Example 1).

[0104] As shown in Example 1 and Comparative Examples 1 and 2, compared to the modified membranes prepared in Comparative Examples 1 and 2, which sequentially laminate TiS2 coatings and ceramic coatings onto the membrane surface, the modified membrane prepared in Example 1, by alternately and staggeredly setting multiple first coating regions containing MS2 and multiple second coating regions containing ceramic particles on the membrane surface, exhibits significantly improved liquid absorption rate, conductivity, and tensile strength. This is because the specially alternately and staggered first and second coating regions not only fully utilize the functional materials in each coating but also further optimize the liquid absorption rate and mechanical properties of the modified membrane.

[0105] Furthermore, as can be seen from Example 1 and Comparative Example 3, the modified membrane prepared by directly mixing two functional materials (MS2 and ceramic particles) and coating them with a modified coating in Comparative Example 3 has performance far inferior to that of Example 1, and even inferior to Comparative Examples 1 and 2. It is speculated that this is because uniform mixing leads to mutual interference between the functions of different functional materials, thus failing to effectively improve the various properties of the modified membrane. While the modified membrane prepared by Comparative Example 4, which alternately sets the first and second coating regions only along the length of the membrane, shows some improvement in performance in terms of liquid absorption rate and conductivity compared to the modified membrane prepared in Comparative Example 3, it is still far inferior to the modified membrane prepared in Example 1, and even slightly inferior to the modified membrane prepared by directly stacking the ceramic coating and the TiS2 coating (Comparative Examples 1 and 2).

[0106] Furthermore, as demonstrated in Examples 1, 8, and Comparative Example 5, the type of functional material in the first coating region of the modified membrane has a significant impact on the liquid absorption rate, conductivity, and other properties of the modified membrane. With all other materials and structures remaining constant, the modified membrane prepared using TiS2 as the functional material (Example 1) exhibits far superior performance compared to the modified membranes prepared using ZrS2 (Example 8) or ZnS (Comparative Example 5). In particular, the performance of the modified membrane prepared using ZnS is significantly reduced, with its liquid absorption rate, conductivity, and tensile strength being less than one-third of those of the modified membrane prepared in Example 1.

[0107] (2) The modified separators prepared in the above examples and comparative examples were used to construct lithium-ion batteries and cycle stability tests were conducted, as follows:

[0108] Preparation of the positive electrode sheet: The positive electrode active material NCM (811), binder polyvinylidene fluoride (PVDF), conductive carbon black and single-walled carbon nanotubes are mixed in a weight ratio of 97.2:1.5:1.2:0.1. N-methylpyrrolidone (NMP) is added and stirred under vacuum until the mixture becomes a uniform and fluid positive electrode slurry. The positive electrode slurry is uniformly coated on the current collector aluminum foil, and then dried, rolled and cut to obtain the desired positive electrode sheet.

[0109] Preparation of negative electrode sheet: Graphite, binder AB-58, CMC and conductive carbon black are mixed in a weight ratio of 96.7:1.5:0.8:1.0, deionized water is added, and the mixture is stirred under vacuum until the mixture becomes a uniform and fluid negative electrode slurry. The negative electrode slurry is uniformly coated on the current collector copper foil, and then dried, rolled and cut to obtain the required negative electrode sheet.

[0110] Diaphragm: The diaphragm used is the modified diaphragm prepared in the above examples and comparative examples.

[0111] Electrolyte: The electrolyte used is 1 mol / L LiPF6, and the solvent of the electrolyte is a mixed solvent obtained by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a mass ratio of 1:1:1.

[0112] A positive electrode, a negative electrode, and a modified separator are assembled into a battery cell by winding. The modified coating side of the modified separator is attached to the negative electrode, and the electrolyte is filled into the battery to obtain the corresponding lithium-ion battery.

[0113] The following electrochemical performance tests were conducted on the lithium-ion batteries prepared with different modified separators, as detailed below:

[0114] Using an electrochemical charge-discharge cabinet, at 25°C, charge the battery cells at a constant current of 0.5C to the upper limit cutoff voltage of 4.3V, and then charge at a constant voltage to a current of 0.05C. After standing for 5 minutes, discharge the battery cells at a constant current of 0.5C to 2.8V. Repeat the above steps until 80% capacity is reached and record the number of cycles.

[0115] The test results are shown in Table 2 below:

[0116] Sample 25℃ cycle / revolution Example 1 1260 Example 2 832 Example 3 820 Example 4 816 Example 5 804 Example 6 790 Example 7 786 Example 8 780 Comparative Example 1 600 Comparative Example 2 530 Comparative Example 3 494 Comparative Example 4 516 Comparative Example 5 400

[0117] As shown in Table 2, compared with the lithium-ion battery constructed by coating the modified separator prepared by directly mixing the two functional materials (TiS2 and ceramic particles) in Comparative Example 3, the lithium-ion batteries constructed by the modified separators prepared in Examples 1-8 exhibit better cycle performance, and are significantly better than the lithium-ion batteries prepared by directly stacking (Comparative Examples 1 and 2) or alternating coating only in the length direction (Comparative Example 4).

[0118] Furthermore, as can be seen from Example 1 and Comparative Example 5, the type of functional material in the first coating region has a significant impact on the battery cycle performance. This is because TiS2 not only helps improve the liquid absorption rate of the separator, but also participates in the construction of the SEI on the negative electrode surface. It can not only enhance the stability of ion conduction and inhibit dendrite growth, but also alleviate the side reactions between the electrode material surface and the electrolyte, thereby improving the battery cycle performance.

[0119] The embodiments described above are merely preferred examples to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.

Claims

1. A modified separator for lithium-ion batteries, characterized in that, The modified diaphragm includes a base membrane and a modified coating disposed on at least one side of the base membrane along its thickness direction; The modified coating includes multiple first coating regions and multiple second coating regions, wherein the first coating regions and the second coating regions are staggered in the length and width directions of the base film; The first coating region contains MS2, where M is selected from one or more metals in group IVB; the second coating region contains ceramic particles; the ceramic particles include one or more of alumina, silicon oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, iron oxide, and titanium oxide. The total area of ​​the plurality of first coating regions accounts for 40%-60% of the total area of ​​the modified coating; MS2 is TiS2; Both the first coating area and the second coating area are rectangles with the same area and a side length of 5-10 mm.

2. The modified separator for lithium-ion batteries according to claim 1, characterized in that, The base film is made of one or more of polyethylene, polypropylene, and polyetherimide. The thickness of the base film is 5-20 μm.

3. The modified separator for lithium-ion batteries according to claim 1, characterized in that, It must contain at least one of the following characteristics: (1) The thickness of the first coating area is 1-20 μm; (2) The thickness of the second coating area is 1-10 μm.

4. The modified separator for lithium-ion batteries according to claim 3, characterized in that, The total area of ​​the plurality of first coating regions is the same as that of the plurality of second coating regions.

5. A method for preparing a modified separator for lithium-ion batteries according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Prepare a first coating slurry and a second coating slurry; the first coating slurry contains MS2, where M is selected from one or more metal elements in group IVB; the second coating slurry contains ceramic particles; S2. The first coating slurry and the second coating slurry are respectively coated on the surface of the base film according to a preset pattern to form a modified coating, and the modified diaphragm is obtained after drying. The preset pattern includes multiple first coating areas and multiple second coating areas; The first coating area is used to coat the first coating slurry, and after drying, the first coating area is formed. The second coating area is used to coat the second coating slurry, which, after drying, forms the second coating area.

6. The preparation method according to claim 5, characterized in that, In step S1, The first coating slurry is obtained by mixing MS2, calcium hydroxide, polyacrylate, carboxymethyl cellulose, and water in a mass ratio of (20-40):(5-6):(4-5):(8-10):(15-30); The second coating slurry is obtained by mixing ceramic particles, calcium hydroxide, polyacrylate, carboxymethyl cellulose and water in a mass ratio of (10-20): (5-6): (4-5): (8-10): (15-30).

7. The preparation method according to claim 5, characterized in that, In step S1, MS2 is TiS2; The preparation method of TiS2 includes the following steps: mixing titanium powder and sulfur powder at a molar ratio of 1:(5-10) to obtain a mixed powder, and then transferring it to an inert atmosphere for heating reaction to obtain TiS2; the heating reaction temperature is 100-150℃, and the heating reaction time is 12-52 h.

8. The preparation method according to claim 5, characterized in that, In step S2, the coating method includes transfer printing and / or spraying, scraping, spin coating or roller coating using a mask.

9. A secondary battery, characterized in that, It includes the modified separator for lithium-ion batteries according to any one of claims 1-4 or the modified separator for lithium-ion batteries prepared by the preparation method according to any one of claims 5-8.

Citation Information

Patent Citations

  • Separator for secondary cell and lithium secondary cell containing thereof

    KR1020100058228A

  • Separators and electrochemical devices comprising the separator

    WO2019034143A1